(untitled) (Observatorio Económico, 2009)
So what will the Central Bank of Chile do to keep the economy going if interest rates cannot fall any further? The Economist explains this point well: that is when the era of unconventional measures begins, such as the desperate issuance of money to sustain the economy’s liquidity at all costs. Continue reading...